34‐3: Visual Sensitivity to "Perfect" Black. Issue 1 (28th June 2021) - Jiang, Fu; Bodner, Ben; Farnand, Susan P.; Murdoch, Michael J.
Abstract : Black level is an important attribute in electronic displays. However, when viewing images, glare impairs sensitivity to black. Previous studies of the impact of glare generally used simple backgrounds, and only simulated image‐based glare. In this study, a psychophysical experiment conducted explores black sensitivity with complex images on OLED displays. The results correlate with an existing glare model [1], provide new black sensitivity data, and serve as the basis for a proposed model predicting black sensitivity for displayed images.